2012
DOI: 10.1016/j.mar.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary performance measurement systems: A review of their consequences and a framework for research

Abstract: a b s t r a c tThe main purpose of this paper is to develop a conceptual framework for understanding the literature on the consequences of contemporary performance measurement (CPM) systems and the theories that explain these consequences. The framework is based on an in-depth review of 76 empirical studies published in high-quality academic journals in the areas of accounting, operations, and strategy. The framework classifies the consequences of CPM into three categories: people's behaviour, organizational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
581
2
56

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 537 publications
(692 citation statements)
references
References 124 publications
(300 reference statements)
18
581
2
56
Order By: Relevance
“…To do so, studies can draw on a variety of psychology theories from cognitive, motivational and social psychology (Birnberg et al, 2007). For example, Franco-Santos et al (2012) identify several psychology theories used to understand the effects of contemporary performance measurement systems, such as information processing, goal setting and justice theories.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, studies can draw on a variety of psychology theories from cognitive, motivational and social psychology (Birnberg et al, 2007). For example, Franco-Santos et al (2012) identify several psychology theories used to understand the effects of contemporary performance measurement systems, such as information processing, goal setting and justice theories.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this review paper is to offer academics and practitioners a dynamic model of managing inter-organizational performance. Our review of background literature identified five approaches that help us deal with disciplinary strands of research pertaining to how organizations create value (Franco-Santos et al, 2012). 26 We thank one of the reviewers for this insight.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in a variety of models (Bititci et al, 2012) that must be interrelated to make conceptual and empirical progress in inter-organizational performance management (Franco-Santos et al, 2012). Our query resulted in the identification of five approaches (Figure 1).…”
Section: Approaches For Studying Inter-organizational Performancementioning
confidence: 99%
See 2 more Smart Citations